Orang Mentawai: Peladang Tradisional dan Ekonomi Pasar - Febrianto, Adri; Fitriani, Erda (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2012)
This article describes the pattern of cultivation, production and distribution of farm fields of the Mentawai society which are based on the results of a research conducted using the perspective of economic anthropology. The study was conducted in eight hamlets. Four separate hamlets in the north and south of Siberut Island, four other separate hamlets in Sipora Island and North Pagai Island. The farming habit of planting various types of plants in the field (mone) to meet the needs of food and cash crops to be sold (commodities for exports) is not focused and can only adapt to the market price and the small quantity of harvest, individually cost them, in contrast to traders who have strategies to anticipate losses due to the fluctuation of price.Key words: traditional cultivation, market